2009
DOI: 10.3171/2008.10.jns08119
|View full text |Cite
|
Sign up to set email alerts
|

Balloon-assisted transarterial embolization of intracranial dural arteriovenous fistulas

Abstract: The BAT provides a new complementary method in the transarterial embolization of DAVFs that are not amenable to transvenous embolization. The venous BAT protects the patency of critical venous pathways, whereas the arterial BAT provides better control of the Onyx-based embolization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
67
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 19 publications
0
67
0
Order By: Relevance
“…Flow control using coils, acrylics, or temporary balloon occlusion is useful for high-flow shunts to decrease the likelihood of distal embolic migration and to improve the penetration of embolic material into the arteriovenous connections. 29 In this series, 9 of 11 patients were cured by endovascular means. Four had curative embolization through a transvenous approach utilizing coils alone or in combination with Onyx.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Flow control using coils, acrylics, or temporary balloon occlusion is useful for high-flow shunts to decrease the likelihood of distal embolic migration and to improve the penetration of embolic material into the arteriovenous connections. 29 In this series, 9 of 11 patients were cured by endovascular means. Four had curative embolization through a transvenous approach utilizing coils alone or in combination with Onyx.…”
Section: Discussionmentioning
confidence: 97%
“…In the current era of Onyx for curative embolization of DAVFs, transarterial endovascular occlusion of fistulous connections is the primary treatment technique. [28][29][30] Transvenous embolization continues to be a safe and effective option if the fistula sites can be approached via an amenable venous pathway, such as the inferior petrosal sinus, facial vein, or the vein of Galen. Incomplete fistula occlusion or cavernous sinus packing alone should be avoided because of potential dangerous flow diversion into cortical or deep veins.…”
Section: Discussionmentioning
confidence: 99%
“…According to our review of the literature, there was no previous report of MMAVF caused by injury of the MMA due to balloon inflation as in our patient. Shi et al 13) reported the effectiveness of proximal occlusion with a balloon (HyperForm; Medtronic, Minneapolis, MN, USA) during TAE for DAVF and suggested a decrease in the shunt flow, improvement in the control of reflux of the embolic agent, and prevention of influx of the embolic agent into so-called dangerous anastomosis as its advantages. Since there have been similar reports using Scepter C (Microvention, Tustin, CA, USA), 14) balloon assistance is an option in treating DAVF.…”
Section: Discussionmentioning
confidence: 99%
“…For DAVFs with high flow, easy reflux or anastomosis with intracranial vessels, it would not be an easy deal to make a better control of Onyx penetration into the fistula. Improper flow or reflux of Onyx may cause unfavorable embolization or even serious complications leaving unexpected prognosis (14).…”
Section: Discussionmentioning
confidence: 99%